Performing Dream Homes
XVI, 238 p. 19 illus.
Keywords: This anthology explores how theatre and performance use home as the prism through which we reconcile shifts in national, cultural, and personal identity. Whether examining parlor dramas and kitchen sink realism, site-specific theatre, travelling tent shows, domestic labor, border performances, fences, or front yards, these essays demonstrate how dreams of home are enmeshed with notions of neighborhood, community, politics, and memory. Recognizing the family home as a symbolic space that extends far beyond its walls, the nine contributors to this collection study diverse English-language performances from the US, Ireland, and Canada. These scholars of theatre history, dramaturgy, performance, cultural studies, feminist and gender studies, and critical race studies also consider the value of home at a time increasingly defined by crises of homelessness — a moment when major cities face affordable housing shortages, when debates about homeland and citizenship have dominated internationalelections, and when conflicts and natural disasters have displaced millions. Global struggles over immigration, sanctuary, refugee status and migrant labor make the stakes of home and homelessness ever more urgent and visible, as this timely collection reveals.